2022
DOI: 10.1021/acsnano.2c09888
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Built-In Electric Field for Efficient Energy Electrocatalysis

Abstract: To utilize intermittent renewable energy as well as achieve the goals of peak carbon dioxide emissions and carbon neutrality, various electrocatalytic devices have been developed. However, the electrocatalytic reactions, e.g., hydrogen evolution reaction/ oxygen evolution reaction in overall water splitting, polysulfide conversion in lithium− sulfur batteries, formation/decomposition of lithium peroxide in lithium−oxygen batteries, and nitrate reduction reaction to degrade sewage, suffer from sluggish kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(76 citation statements)
references
References 216 publications
0
76
0
Order By: Relevance
“…[19] Herein, we designed a core-shell heterostructure with n-type ZnO and p-type SACs. The p-n heterojunction creates built-in electric field (BIEF) to form a space-charged (or depletion) region, [20] which spontaneously drives the directional electrons/holes separation and diffuse toward the positively and negatively charged layers. The efficient interfacial charge communication leads to the spatial charge redistribution, which modulates the local electronic structure of the MÀ N x with higher intrinsic activity.…”
Section: Resultsmentioning
confidence: 99%
“…[19] Herein, we designed a core-shell heterostructure with n-type ZnO and p-type SACs. The p-n heterojunction creates built-in electric field (BIEF) to form a space-charged (or depletion) region, [20] which spontaneously drives the directional electrons/holes separation and diffuse toward the positively and negatively charged layers. The efficient interfacial charge communication leads to the spatial charge redistribution, which modulates the local electronic structure of the MÀ N x with higher intrinsic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The heterojunction has a typical Schottky contact rectification curve, which indicates that the built-in electric field (E B ) direction formed at the 2H-MoS 2 / Ta 4 C 3 interface is from Ta 4 C 3 to 2H-MoS 2 . [38,39] In addition, previous studies have demonstrated that the induced electric field (E CE ) generated by contact electrification also influences the motion of the heterointerface carriers. [23,26,40] To obtain the direction of the induced electric field, the change of the surface potential of 2H-MoS 2 during the friction process between 2H-MoS 2 and Ta 4 C 3 was tested, as shown in Figure 2D, the surface of 2H-MoS 2 was negatively charged, which indicates that there is contact initiation to induce the direction of the induced electric field from Ta 4 C 3 to 2H-MoS 2 .…”
Section: Mechanism and Electrical Output Of Mtngsmentioning
confidence: 99%
“…To smoothly bolster the adsorption-diffusion-conversion process of LiPSs at the interface of the heterostructure, [15,52] the formed built-in EF is usually intertwined with the charge redistribution caused by spontaneous electron transport at the interface, exerting an additional degree of freedom to tune the interfacial electron density, manipulate the charge transfer, and modulate the targeted ion adsorption. [25,[53][54][55] As a representative, when p-type (a semiconductor with holes as majority carriers) and n-type (a semiconductor with electrons as majority carriers) semiconductors have a favorable lattice match and different Fermi energy levels (E F ), the electrons and holes would reversely diffuse and cross the interface until the two levels are aligned, thus generating a built-in EF (Figure 2D). [25,56] In concomitance with favored interfacial chargetransfer kinetics, the anisotropic characteristics are empowered to different components to fully ignite the consecutive adsorption-diffusion-catalysis process of LiPSs on the interface of heterojunctions.…”
Section: Interfacial Charge Transfer Elevated By a Built-in Efmentioning
confidence: 99%